Turning ourselves inside out : thriving Christian communities - Daye, Russell; Fennell, Robert C. (Fortress Press, 2021)
Turning Ourselves Inside Out emerges from the Thriving Christian Communities Project started by the authors in 2015. In interviews with thirty-five faith communities, the authors discovered that amid great upheaval, Christ is giving us a new church. This book invites readers to listen to others' experiences and then dig deep into their own and get down to the business of dreaming God's dream and making it real.